Pengaruh Peran Penyuluh Terhadap Pengembangan Kelompok Tani Hortikultura di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - aisyah, Aisyah; Yulida, Roza; Novian, Novian (Fakultas Pertanian Universitas Jember, 2024)
For farmers and their families, agricultural extension serves as informal education. Through extension activities, agricultural extension workers are expected to improve human resources in agriculture and also provide infrastructure and facilities for farmers. The function of extension workers in building farmer groups has an impact on the level of development of these groups. This study aims to determine how the influence of the role of extension workers on the development of horticultural farmer groups in Kuantan Mudik District. This research was conducted in Kuantan Mudik District, Kuantan Singingi Regency. All horticultural farmer groups in Kuantan Mudik District became the study population. Sampling was done with multi-stage random sampling technique and obtained as many as 60 respondent farmers calculated using the Slovin formula. Interview-based survey is the research methodology used. Data were analyzed by Structural Equation Model (SEM) using SmartPLS and descriptive analysis. The results showed that the role of extension agents consisting of facilitators, innovators, motivators, dynamicators, educators, and consultants had a positive and significant effect on the development of horticultural farmer groups which included routine activities and division of tasks, adequate facilities, farming experience, group norms and rules, and group achievement. The R Square value of 0.719 or 71.9% indicates that 71.9% of farmer group development is influenced by the role of extension agents, and the remaining 28.1% is influenced by other factors not examined in this study.